European Cultural Diplomacy and Arab Christians in Palestine, 1918-1948 Between Contention and Connection - Sanchez Summerer, Karène; Zananiri, Sary (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access book investigates the transnationally connected history of Arab Christian communities in Palestine during the British Mandate (1918-1948) through the lens of the birth of cultural diplomacy. Relying predominantly on unpublished sources, it examines the relationship between European cultural agendas and local identity formation processes and discusses the social and religious transformations of Arab Christian communities in Palestine via cultural lenses from an entangled perspective. The 17 chapters reflect diverse research interests, from case studies of individual archives to chapters that question the concept of cultural diplomacy more generally. They illustrate the diversity of scholarship that enables a broad-based view of how cultural diplomacy functioned during the interwar period, but also the ways in which its meanings have changed. The book considers British Mandate Palestine as an internationalised node within a transnational framework to understand how the complexity of cultural interactions and agencies engaged to produce new modes of modernity. Karène Sanchez Summerer is Associate Professor at Leiden University, The Netherlands. Her research considers the European linguistic and cultural policies and the Arab communities (1860-1948) in Palestine. She is the PI of the research project (2017-2022), 'CrossRoads: European Cultural Diplomacy and Arab Christians in Palestine (1918-1948)' (project funded by The Netherlands National Research Agency, NWO). She is the co-editor of the series 'Languages and Culture in History' with W. Frijhoff, Amsterdam University Press. She is part of the College of Experts: ESF European Science Foundation (2018-2021). Sary Zananiri is an artist and cultural historian.He is currently a Postdoctoral Fellow on the NWO funded project 'CrossRoads: European Cultural Diplomacy and Arab Christians in Palestine (1918-1948)' at Leiden University, The Netherlands.